The Relationship Between The Quality Of Physiotherapy Services To The Level Of Patient Satisfaction With Physiotherapy Independent Practice Sport Cases In Malang Raya - An Nisaa Primastuti Suhardi Putri; Safun Rahmanto; Dimas Sondang Irawan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
The development of physiotherapy services in Malang Raya is urgently needed in order to meet the demand for physiotherapy medical personnel in line with the high development of people's lifestyles. The quality of service obtained is a patient's assessment on the basis of conformity between customer perceptions and their expectations regarding the services provided. This study aims to determine the relationship between the quality of physiotherapy services and the level of patient satisfaction in sport cases of independent practice of physiotherapy in Malang Raya. This study used the SERVQUAL questionnaire to assess service quality and the MedRisk questionnaire to assess physical therapy patient satisfaction. The sampling technique used is convenience sampling in which samples are taken if they are willing to be respondents. The results of this study showed that the normality test for the SERVQUAL variables was 0.068 and MedRisk 0.099, meaning that both variables were normal. The correlation test using Pearson obtained a value of 0.000 (<0.05) which concluded that there was a relationship between the two variables. The results show that there is a relationship between the quality of physiotherapy services and the satisfaction of sports case patients in independent practice of physiotherapy. The higher the value of service quality obtained, the higher the value of patient satisfaction and vice versa.